THE LOCAL DWARF GALAXIES:BUILDING BLOCKS OFMASSIVE ONES? I.THE FORNAX DWARF GALAXY - Nykytyuk, T. V. (Одеські астрономічні публікації, 2008)
A chemical evolution of the Local Group dwarf galaxy Fornax is considered in the framework of the merger scenario. We suppose a galactic stellar halo to be formed as separate fragments which then merge; thus, we can calculate the set of such the fragments to reproduce the observed metallicity distribution function of a galaxy. Accordingly, if dwarf galaxies were such the systems, which, once merged, have formed massive galaxies, we need to obtain only one fragment to reproduce the observed metallicity distribution function of a dwarf galaxy. To test this assumption, the stellar metallicity distribution functions of Fornax was calculated in the framework of the merger scenario. The more than one fragment was obtained for galaxy under consideration; thus, it is unlikely the systems similar to Fornax to be building blocks of massive galaxies.